PENGARUH AKUNTABILITAS, TRANSPARANSI DAN KUALITAS PELAYANAN LEMBAGA PENGELOLA ZAKATTERHADAP KOMITMEN MUZAKKI: KEPERCAYAAN MUZAKKISEBAGAI VARIABEL INTERVENING - Eha - Nugraha (Department of Accounting, Faculty of Economics, Universitas Sriwijaya, 2019)
This research aims to find empirical evidence of the influence of accountability on Muzakki Trust, transparency on Muzakki Trust, quality of service to trust Muzakki and trust Muzakki to the commitment of Muzakki in To pay zakat with the trust of Muzakki as a variable intervening. The research uses primary data obtained from questionnaires aimed to Muzakki at Rumah Zakat institutions, DPUDT and PKU in the Bandarlampung area. The sample determination in this study uses convenience sampling with Quota Sampling correction. The questionnaire was spread over 120 questionnaires and 91 questionnaires returned. From 91 questionnaires there were 8 questionnaires that could not be processed because there were some statements that were not answered by the respondents, so that only 83 questionnaires could be processed and analyzed. The survey time was spread for almost two months. This is because it adjusts the schedule of the meeting of Zakat institutions with their muzakki. Data is processed using Smart-PLS and SPSS version 18. Results show accountability variables and significant service quality, whereas transparency variables do not significantly influence the trust and commitment of Muzakki.